Polyphenol oxidase affects normal nodule development in red clover (Trifolium pratense L.) - Webb, K. Judith; Cookson, Alan; Allison, Gordon; Sullivan, Michael L.; Winters, Ana L. (Frontiers in Plant Science, 2014)
Polyphenol oxidase (PPO) may have multiple functions in tissues depending on its cellular or tissue localisation. Here we use PPO RNAi transformants of red clover (Trifolium pratense) to determine the role PPO plays in normal development of plants, and especially in N2-fixing nodules. In red clover, PPO was not essential for either growth or nodule production, or for nodule function in plants grown under optimal, N-free conditions. However, absence of PPO resulted in a more reduced environment in all tissues, as measured by redox potential, and caused subtle developmental changes in nodules. Leaves and, to a lesser extent nodules, lacking PPO tended to accumulate phenolic compounds. A comparison of nodules of two contrasting clones by microscopy revealed that nodules lacking PPO were morphologically and anatomically subtly altered, and that phenolics accumulated in different cells and tissues. Developing nodules lacking PPO were longer, and there were more cell layers within the squashed cell layer (SCL), but the walls of these cells were less thickened and the cells were less squashed. Within the N2-fixing zone, bacteroids appeared more granular and were less tightly packed together.